Providence. Act 1 - Moore, Alan, 1953- (Avatar Press, 2017)
Alan Moore's quintessential horror series has set the standard for a terrifying examination of the works of H.P. Lovecraft. It is being universally hailed as one of Moore's most realized works in which the master scribe has controlled every iota of the story, art, and presentation. The result has been a masterpiece like no other, unparalleled in tone and content, and a true must have addition to his essential works in the field.